2014
DOI: 10.1248/bpb.b13-00667
|View full text |Cite
|
Sign up to set email alerts
|

20(<i>S</i>)-Ginsenoside Rh2 Induces Apoptosis in Human Leukaemia Reh Cells through Mitochondrial Signaling Pathways

Abstract: 20(S)-Ginsenoside

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…These data suggested that ginsenosides 20(S)-Rh2, Rk2, Rh3, and Rh2-MIX possess anti-cancer effect on the B16F10, MDA-MB-231, and HuH-7 cancer cell lines. This anti-cancer effect was very similar to that disclosed in a previous report [9][10][11][12][13][14]. By contrast, 20(R)- Rh2 did not inhibit B16F10, MDA-MB-231, and HuH-7 cancer cell growth at various concentration ranges within 24 h ( Fig.…”
Section: Scaled-up Production Of Ginsenoside Rh2-mix With Purificationsupporting
confidence: 90%
See 1 more Smart Citation
“…These data suggested that ginsenosides 20(S)-Rh2, Rk2, Rh3, and Rh2-MIX possess anti-cancer effect on the B16F10, MDA-MB-231, and HuH-7 cancer cell lines. This anti-cancer effect was very similar to that disclosed in a previous report [9][10][11][12][13][14]. By contrast, 20(R)- Rh2 did not inhibit B16F10, MDA-MB-231, and HuH-7 cancer cell growth at various concentration ranges within 24 h ( Fig.…”
Section: Scaled-up Production Of Ginsenoside Rh2-mix With Purificationsupporting
confidence: 90%
“…Rh2 can inhibit the growth of many kinds of cancer cells, including breast cancer, prostate cancer, hepatoma, gastric cancer, colon carcinoma, and pancreatic cancer [10]. For example, the ginsenoside 20(S)-Rh2 has anti-cancer effects in the human acute leukemia cell line Reh via a mechanism involving mitochondrial cytochrome c and activation of caspase-9 and caspase-3 [11]. Rh2 was also shown to induce apoptosis of the human hepatoma cell line SK-HEP-1 by the activation of caspase-8 and caspase-9 [12], and to inhibit migration of HepG2 cells by inhibiting the expression of MMP3 at the mRNA and protein levels [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenoside Rh2 is a potent anticancer compound targeting multiple cancers [11,13,[15][16][17][18][19]26,27]. Recent reports suggested that ginsenoside Rh2-induced apoptosis in human leukemia cell via mitochondrial signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports suggested that ginsenoside Rh2-induced apoptosis in human leukemia cell via mitochondrial signaling pathways. Following the up-regulation of Bax and Bak, cytochrome c was released from mitochondria into cytoplasm and caspase 3 was activated following cleavage of pro-caspase 8 and procaspase 9 [26,28]. In this study, the overexpression of TNF-α in Rh2-treated HL-60 cells was examined by high-throughput screening using microarray technology.…”
Section: Discussionmentioning
confidence: 99%
“…As a step in overcoming this limitation in chemotherapy, medicines prepared from natural traditional Chinese medicine (TCM) are currently being considered as anticancer agents (3,4). In the past decades, a series of studies have demonstrated that many extracted products from natural plants can kill cancer cells including leukemia cells in vitro (5).…”
Section: Introductionmentioning
confidence: 99%